Hubungan Kepadatan Koperasi dan Keputusan Mengakses Pembiayaan Koperasi - Nopitasari Nopitasari; Dwini Handayani (Pusat Penelitian, Badan Keahlian DPR RI, 2020)
Cooperative is a financial institution capable of providing financing for MSMEs which are still constrained by capital problems. Many MSMEs are constrained by financing problems, this indicates high demand for funding but there is a limited number of cooperative which can provide financing for MSMEs. Indonesia has the largest area where Cooperative is not spread evenly so that many households have difficulties in accessing financing from Cooperative. In this study, Cooperatives’ accessibility is proxied to its density. The purpose is to identify the relationship between the density of cooperatives and the decision to access Cooperative financing by using Susenas of March 2018 data and a sample of 283,478 households. By identifying the relationship, it would be recognizable whether Cooperative is still becoming a financing alternative or not. Based on the results of the Multinomial Logit Regression, the density of Cooperative is related to the decision of households to access financing from Cooperative. The density of cooperative improves the decision taken by households to access financing from Cooperative. The increase in the number of cooperatives will increase financial inclusion as well, which is helpful for people who need loans. The Indonesian government needs to conduct cooperative development programs to increase financial inclusion. However, the density of Cooperative doesn’t significantly influence the household decision to access financing from institutions other than cooperative. Thus, cooperative development programs should be implemented in areas where there are no financial institutions yet.Keywords: cooperative, microfinance, access to finance, householdAbstrakKoperasi merupakan salah satu lembaga keuangan yang dapat memberikan pembiayaan bagi Usaha Mikro, Kecil dan Menengah (UMKM) yang masih terkendala masalah modal. Banyaknya jumlah UMKM yang terkendala masalah pembiayaan mengindikasikan terdapat banyaknya permintaan akan pembiayaan namun belum diimbangi dengan jumah koperasi yang dapat memberikan pembiayaan kepada UMKM. Indonesia memiliki wilayah yang sangat luas, saat ini sebaran koperasi belum merata ke setiap wilayah Indonesia sehingga banyak rumah tangga yang terkendala aksesiblitas untuk mengakses pembiayaan koperasi. Pada penelitian ini aksesibilitas koperasi diproksikan dengan kepadatan koperasi. Pada penelitian ini bertujuan mengidentifikasi hubungan antara kepadatan koperasi terhadap keputusan mengakses pembiayaan koperasi dengan data Susenas Maret 2018 dan sampel sebanyak 283.478 rumah tangga. Dengan mengidentifikasi hubungan tersebut, dapat diketahui apakah koperasi masih menjadi salah satu alternatif pilihan pembiayaan atau bukan. Berdasarkan hasil regresi Multinomial Logit menunjukkan bahwa kepadatan koperasi mempunyai hubungan terhadap keputusan rumah tangga mengakses pembiayaan di koperasi. Kepadatan koperasi meningkatkan keputusan mengakses pembiayaan pada rumah tangga di koperasi. Bertambahnya jumlah koperasi akan meningkatkan inklusi keuangan sehingga dapat membantu masyarakat yang membutuhkan pinjaman. Pemerintah perlu melakukan program penumbuhan koperasi di Indonesia dalam rangka peningkatan inklusi keuangan. Namun kepadatan koperasi tidak berpengaruh secara signifikan terhadap keputusan rumah tangga mengakses pembiayaan di selain koperasi, sehingga program penumbuhan koperasi sebaiknya dilakukan pada daerah yang belum terdapat lembaga keuangan pada daerah tersebut.Kata kunci: koperasi, keuangan mikro, akses pembiayaan, rumah tangga